Respuesta :
a.
[tex]x^{11}=13\pmod{35}\implies\begin{cases}x^{11}\equiv13\equiv3\pmod5\\x^{11}\equiv13\equiv6\pmod7\end{cases}[/tex]
By Fermat's little theorem, we have
[tex]x^{11}\equiv (x^5)^2x\equiv x^3\equiv3\pmod5[/tex]
[tex]x^{11}\equiv x^7x^4\equiv x^5\equiv6\pmod 7[/tex]
5 and 7 are both prime, so [tex]\varphi(5)=4[/tex] and [tex]\varphi(7)=6[/tex]. By Euler's theorem, we get
[tex]x^4\equiv1\pmod5\implies x\equiv3^{-1}\equiv2\pmod5[/tex]
[tex]x^6\equiv1\pmod7\impleis x\equiv6^{-1}\equiv6\pmod7[/tex]
Now we can use the Chinese remainder theorem to solve for [tex]x[/tex]. Start with
[tex]x=2\cdot7+5\cdot6[/tex]
- Taken mod 5, the second term vanishes and [tex]14\equiv4\pmod5[/tex]. Multiply by the inverse of 4 mod 5 (4), then by 2.
[tex]x=2\cdot7\cdot4\cdot2+5\cdot6[/tex]
- Taken mod 7, the first term vanishes and [tex]30\equiv2\pmod7[/tex]. Multiply by the inverse of 2 mod 7 (4), then by 6.
[tex]x=2\cdot7\cdot4\cdot2+5\cdot6\cdot4\cdot6[/tex]
[tex]\implies x\equiv832\pmod{5\cdot7}\implies\boxed{x\equiv27\pmod{35}}[/tex]
b.
[tex]x^5\equiv3\pmod{64}[/tex]
We have [tex]\varphi(64)=32[/tex], so by Euler's theorem,
[tex]x^{32}\equiv1\pmod{64}[/tex]
Now, raising both sides of the original congruence to the power of 6 gives
[tex]x^{30}\equiv3^6\equiv729\equiv25\pmod{64}[/tex]
Then multiplying both sides by [tex]x^2[/tex] gives
[tex]x^{32}\equiv25x^2\equiv1\pmod{64}[/tex]
so that [tex]x^2[/tex] is the inverse of 25 mod 64. To find this inverse, solve for [tex]y[/tex] in [tex]25y\equiv1\pmod{64}[/tex]. Using the Euclidean algorithm, we have
64 = 2*25 + 14
25 = 1*14 + 11
14 = 1*11 + 3
11 = 3*3 + 2
3 = 1*2 + 1
=> 1 = 9*64 - 23*25
so that [tex](-23)\cdot25\equiv1\pmod{64}\implies y=25^{-1}\equiv-23\equiv41\pmod{64}[/tex].
So we know
[tex]25x^2\equiv1\pmod{64}\implies x^2\equiv41\pmod{64}[/tex]
Squaring both sides of this gives
[tex]x^4\equiv1681\equiv17\pmod{64}[/tex]
and multiplying both sides by [tex]x[/tex] tells us
[tex]x^5\equiv17x\equiv3\pmod{64}[/tex]
Use the Euclidean algorithm to solve for [tex]x[/tex].
64 = 3*17 + 13
17 = 1*13 + 4
13 = 3*4 + 1
=> 1 = 4*64 - 15*17
so that [tex](-15)\cdot17\equiv1\pmod{64}\implies17^{-1}\equiv-15\equiv49\pmod{64}[/tex], and so [tex]x\equiv147\pmod{64}\implies\boxed{x\equiv19\pmod{64}}[/tex]